Grandparents perception on the value of play - Idanan, Norraine R.
This qualitative research studied the current perceptions on the value of play among Filipino grandparents, the activities they consider as play, and the role of play in the grandparent-grandchild relationship. Judgement and snowball sampling were used to acquire thirty grandparents aged sixty-three to seventy five years residing in Quezon City and Cainta, Rizal. A grandparent profile questionnaire, interview schedule and a Likert scale survey were used for data collection in the respondents' homes. The findings of this study relate a highly positive regard on the value of play. Five themes emerged for the grandparents' perceptions of play namely; recreation/enjoyable activities, part of social development, enhances physical development, tool for holistic development, and facilitates cognitive development. A healthy and close relationship shared by the grandparent and grandchild was revealed because most of the respondents engaged in different forms of play. Three themes emerged for the activities the grandparent's consider as namely: physical, cognitive, and creative play. Similarly, three themes emerged for the effect of play to the relationship namely: closer relationship, sharing values, and bonding. The discussion of the results established the soundness of the conceptual framework of the study where a bidirectional relationship is observed between the grandparent's perception on the value of play and the grandparent-grandchild relationship. Further research may consider evaluating the factor on the sex of the respondents and gender differences on responses. Gender bias on toys may also be considered for further research.